A modified neighborhood preserving embedding-based incipient fault detection with applications to small-scale cyber–physical systems. (September 2020) - Chen, Hongtian; Wu, Jianping; Jiang, Bin; Chen, Wen
Abstract: Industrial cyber–physical systems (ICPSs) are backbones of the Industrial 4.0 where control, physical entities, and monitoring are intensively interacted. Aiming to improve safety of a small-scale ICPS whose physical entity is an electrical drive system, this paper will develop a new detection strategy for incipient faults in neighborhood preserving embedding (NPE) framework that can provide stable solutions. The proposed modified NPE can not only extract local information effectively on data manifold of the ICPS but also solve the singularity problem caused by generalized eigenvalue decomposition skills. Additional advantages of this design for ICPSs include the enhanced fault detectability, inherent scalability, and accelerated computation efficiency. The proposed method is firstly evaluated by mathematical deviations and then is evaluated by its application to a small-scale ICPS. Three sets of experimental results show the efficacy of the proposed method in dealing with online detection of incipient faults in the ICPS. Highlights: A small-scale ICPS for an electrical drive system is designed, where real-time control and system monitoring are integrated in the cyber system. A novel FD solution based on modified NPE is proposed to achieve enhanced fault detectability accelerate computation efficiency.